Synthesis and structural features of slab structure SrLa1−xSmxInO4 - Titov, Y.A.; Belyavina, N.M.; Slobodyanik, M.S.; Chumak, V.V.; Timoschenko, M.V.; Tomazenko, L.V. (Reports of the National Academy of Sciences of Ukraine, 2019)
The substitution conditions of La by Sm atoms in the slab perovskite-like structure (SPS) of SrLa1−xSmxInO4 (0 ≤ x ≤ 0.4) indates are determined. Orthorhombic (sp. gr. Pbca) crystal structures of SrLa1−xSmxInO4 phases with x = 0.2 and 0.4 are determined, by using the X-ray powder diffraction methods. Analysis of the obtained data has shown that, in a case of the substitution of La atoms by Sm atoms in SPS of SrLa1−xSmxInO4, a gradual reduction of the deformation degree of interblock (Sr, La, Sm)О9 polyhedra and the average In—O distance in InO6 octahedra takes place. Length of (Sr, La, Sm)–О2 interblock bonds is significantly increased. Increase in the distance between perovskite-like blocks reduces a durability of their bonding. This results in the destruction of SPS and a limitation of the area of SrLa1−xSmxInO4 solid solutions with SPS.